The Ralization on the poetry of Ibn Hareq Al-Balansi - عبد الله برهان صفاء (Journal of College of Education, 2020)
This Realization on the poetry of Ibn Hareq Al-Balansi (d. 622 AH), which was collected for the first time by Dr. Muhammad bin Sharifa, a quarter of a century ago, and he had the merit of introducing this great Andalusian writer at that time, and presenting it to those interested in Arab heritage in general. And researchers in Andalusian affairs in particular. So this realization complemented and corrected what was presented by the Ibn Sharifah, adding to his previous work new verses of poetry, which had not previously been published in that total, and it is a natural matter when the tools and the happiness of the means that exist in time are available, according to what appears to exist from the manuscripts and what is published from them, calculated For centuries, it was within the lost and lost, and some of it related to the subject of this realization, and it appeared to us from the poetry of Ibn Hareq that there was a reason to a realization. To clarify a summary of the features of that poetry.